CT Imaging Findings after Stereotactic Radiotherapy for Liver Tumors - Olga R. Brook; Eavan Thornton; Mishal Mendiratta-Lala; Anand Mahadevan; Vassilious Raptopoulos; Alexander Brook; Robert Najarian; Robert Sheiman; Bettina Siewert (Gastroenterology Research and Practice)
Purpose. To study radiological response to stereotactic radiotherapy for focal liver tumors. Materials and Methods. In this IRB-approved, HIPAA-compliant study CTs of 68 consecutive patients who underwent stereotactic radiotherapy for liver tumors between 01/2006 and 01/2010 were retrospectively reviewed. Two independent reviewers evaluated lesion volume and enhancement pattern of the lesion and of juxtaposed liver parenchyma. Results. 36 subjects with hepatocellular carcinoma (HCC), 25 with liver metastases, and seven with cholangiocarcinoma (CCC) were included in study. Mean follow-up time was 5.6 ± 7.1 months for HCC, 6.4 ± 5.1 months for metastases, and 10.1 ± 4.8 months for the CCC. Complete response was seen in 4/36 (11.1%) HCCs and 1/25 (4%) metastases. Partial response (>30% decrease in long diameter) was seen in 25/36 (69%) HCCs, 14/25 (58%) metastases, and 7/7 (100%) of CCCs. Partial response followed by local recurrence (>20% increase in long diameter from nadir) occurred in 2/36 (6%) HCCs and 4/25 (17%) metastases. Liver parenchyma adjacent to the lesion demonstrated a prominent halo of delayed enhancement in 27/36 (78%) of HCCs, 19/21 (91%) of metastases, and 7/7 (100%) of CCCs. Conclusion. Sustainable radiological partial response to stereotactic radiotherapy is most frequent outcome seen in liver lesions. Prominent halo of delayed enhancement of the adjacent liver is frequent finding.